Potential Immunomodulatory Activity of a Selected Strain Bifidobacterium bifidum H3-R2 as Evidenced in vitro and in Immunosuppressed Mice - Shang, Jiacui; Wan, Feng; Zhao, Le; Meng, Xiangchen; Li, Bailiang (Frontiers in Microbiology, 2020)
The microbiota is directly involved in the development and modulation of the intestinal immune system. In particular, members of the genus Bifidobacterium play a primary role in immune regulation. In the present study, Bifidobacterium bifidum H3-R2 was screened from 15 bifidobacterium strains by in vitro experiment, showing a positive tolerance to digestive tract conditions, adhesion ability to intestinal epithelial cells and a regulatory effect on immune cell activity. Immunostimulatory activity of B. bifidum H3-R2 was also elucidated in vivo in cytoxan (CTX)-treated mice. The results showed that the administration of B. bifidum H3-R2 ameliorated the CTX-induced bodyweight loss and imbalanced expression of inflammatory cytokines, enhanced the production of secretory immunoglobulin A (SIgA), and promoted splenic lymphocyte proliferation, natural killer (NK) cell activity and phagocytosis of macrophages in immunosuppressed mice. In addition, B. bifidum H3-R2 restored injured intestinal mucosal, and increased the villus length and crypt depth in CTX-treated mice. The results could be helpful for understanding the functions of B. bifidum H3-R2, supporting its potential as a novel probiotic for immunoregulation.